Construction of raft foundation / Muhammad Adam Azrai Abdul Rahman - Abdul Rahman, Muhammad Adam Azrai (Universiti Teknologi MARA, Perak, 2019)
A raft foundation is basically a thick reinforced concrete slab laying on large area of ground reinforced with steel bars that supports the column or wall and transfer the load to the ground. Raft foundation basically used to support structures like residential and commercial building where the soil condition of the area is soft and poor. This type of foundation will be used when the floor areas are small and structural loading are low such as in one or two-storey residential construction. Raft foundations can be fast and cost-saver to construct, because they did not required deep excavations compared to strip or pad foundations.